Hybrid finishing coatings applied on laminar zinc primers - Giudice, Carlos Alberto (2013)
Hybrid finishing coatings were formulated with several film-forming materials and reinforcement fibers. In all cases, the same tri-pigmented epoxy-polyamide coating based on laminar zinc was used as primer. The results indicated that well-wetted fibers improved mechanical properties of finishing coating films, such as tensile strength, modulus of elasticity, hardness, adhesion, and impact resistance; on the other hand, elongation decreased according with type and level of reinforcement fibers selected. In addition, finishing coatings with semiconductive fibers displayed in salt spray (fog) apparatus, a high dissolution of metallic zinc of primer since these fibers would act as cathode in galvanic cells. According to IR spectrum analysis, chemical degradation was observed only in coatings with the binder susceptible to basic hydrolysis due to the action of hydroxyl ions formed on semiconductive fibers. Furthermore, nonconductive fibers included in finishing coatings displayed no changes in any film-forming material (even when alkyd resin was used) nor promoted excessive zinc dissolution of primer.